2021
DOI: 10.1007/s12144-021-02197-2
|View full text |Cite
|
Sign up to set email alerts
|

Give me your password! What are you hiding? Associated factors of intimate partner violence through technological abuse

Abstract: The present study explored the associated factors of intimate partner violence through technological abuse (ITPV) in a sample of 1113 participants aged 18 to 65 (71.3% females). Our research’s primary questions were the following: 1). Is there a significant link between relationship attachment styles and ITPV perpetration or victimization?; 2). Is there a significant link between participants’ demographic and relationship characteristics (i.e., relationship length and partners’ fidelity), online behavior (i.e.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 81 publications
0
9
0
Order By: Relevance
“…For instance, a major source of stress for victims is economic violence, one of the least studied forms of violence and often included in emotional or psychological abuse, encompasses controlling and limiting access to nancial resources, denying access to needs (e.g., food, clothing, medication), tracking the use of money and also withholding or hiding the money earned together 30 . Digital (or technological) intimate partner violence provides a quick and easy method of harassing women, using social media, GPS tracking, constant texting, or other forms of intimidation, embarrassment, and control, and it has been described as more frequent due to the COVID-19 pandemic 31 . Therefore, digital violence is a type of violence that deserves to be further studied through comparative analyzes before and after the pandemic, and our study portrays the prevalence in the year just before the pandemic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, a major source of stress for victims is economic violence, one of the least studied forms of violence and often included in emotional or psychological abuse, encompasses controlling and limiting access to nancial resources, denying access to needs (e.g., food, clothing, medication), tracking the use of money and also withholding or hiding the money earned together 30 . Digital (or technological) intimate partner violence provides a quick and easy method of harassing women, using social media, GPS tracking, constant texting, or other forms of intimidation, embarrassment, and control, and it has been described as more frequent due to the COVID-19 pandemic 31 . Therefore, digital violence is a type of violence that deserves to be further studied through comparative analyzes before and after the pandemic, and our study portrays the prevalence in the year just before the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Digital (or technological) IPV provides a quick and easy method of harassing women via social media, GPS tracking, constant texting, or other forms of intimidation, embarrassment, and control. This type of violence has been described as more frequent due to the COVID-19 pandemic (Maftei & Dănilă, 2021). Digital violence is a type of violence that deserves to be further studied via comparative analyses before and after the pandemic; our study portrays the prevalence in the year just before the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…A more recent review by Newman and their collaborators [31] indicated several factors at both teams and organizational levels and personal characteristics such as low empathy, male gender, and cynicism that would further lead to various deviant behaviors. Regardless of the working model, the related research highlights the various adverse effects of moral disengagement, e.g., aggression, bullying, cyber aggression, and antisocial behavior, in general [32][33][34][35]. Thus, extending and adding to the previous findings related to the predictors and mediators of moral disengagement is all the more important.…”
Section: Moral Disengagement Intolerance Of Uncertainty and Compassionmentioning
confidence: 98%
“…The detrimental effects of moral disengagement have been assessed in various studies, all of them highlighting the importance of further exploring the potential predictors and associated factors of these cognitive mechanisms [32][33][34][35]. However, the specific indirect effect of moral disengagement on katagelasticism has not yet been investigated when discussing compassion.…”
Section: The Present Studymentioning
confidence: 99%
“…The extant scientific literature presents conclusive evidence regarding the strong association between moral disengagement mechanisms and bullying (Romera et al, 2019) and cyberbullying (Lo Cricchio et al, 2021). The association between this cognitive process and dating violence has been less explored, and the results point to a moderate relationship between these two variables (Maftei & Dănilă, 2021; Rubio-Garay et al, 2019; Sánchez-Jiménez & Muñoz-Fernández, 2021). A recent study (Sánchez-Jiménez et al, 2021) found that adolescents with high levels of moral disengagement perceived online control as less aggressive than their counterparts with low levels.…”
Section: The Contribution Of Moral Disengagement To the Understanding...mentioning
confidence: 99%